Towards inventory and assessment of plant resources of Bangladesh: challenges and prospects - Rahman, MA (Journal of Biodiversity Conservation and Bioresource Management, 2021)
This review is to appraise plant resources of Bangladesh. Contributions to the inventory, flora writing and establishment of National Herbarium in the country are discussed. The progress of Published Flora of Bangladesh since its independence with family name, number of genera and species including contributors‟ name is mentioned. Contributions of the botanists of the Dhaka University (DU), Chittagong University (CU), Jahangirnagar University (JU), Rajshahi University (RU), Bangladesh Forest Research Institute (BFRI), Bangladesh Council of Scientific and Industrial Research (BCSIR), Asiatic Society of Bangladesh and other institutions in botanical explorations and inventory of the flora are also mentioned. Assessment of threatened taxa, medicinal plant diversity, new discovery, new records, endemics, and production of Red Data Book are also considered as valuable entry in this study. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(1): 47-58